The effect of melatonin on procarbazine induced testicular toxicity on rats. (December 2014) - Alp, Bilal Fırat; Kesik, Vural; Malkoç, Ercan; Yiğit, Nuri; Saldır, Mehmet; Babacan, Oğuzhan; Akgül, Emin Özgür; Poyrazoglu, Yavuz; Korkmazer, Nadir; Gulgun, Mustafa; Erdem, Onur
Abstract Procarbazine (P) is an effective chemotherapeutic drug especially used in lymphoma treatment; however testicular toxicity is a limiting factor. Various ways of treatment were tried to preserve testicular function including hormonal treatment, antioxidant treatment, and sperm cryopreservation but resulted with low rates of satisfaction. Procarbazine is a well known agent causing sterility even in the first doses of chemotherapy. Antioxidants such as N acetylcysteine and ascorbate have been used for protective purposes and were very successful. Melatonin (M) is another powerful antioxidant and we aimed to use M for the protection of P induced testicular toxicity in this study. Procarbazine was given peroral by gavage once a week at a dose of 62.5 mg/kg/week for 4 weeks (total dose: 250 mg/kg) (P group) and in procarbazine + melatonin (PM) group, 10 mg/kg melatonin was intraperitoneally administered daily for five days a week for 4 weeks (total 20 days). The experiment ended at day 90. In the P and PM groups the testicle width, length, and weight, sperm A and sperm AB properties (Sperm A: sperms straight line progressive, Sperm B: sperms straight slow progressive, Sperm AB: Sperm A + Sperm B), spermatogonia, Sertoli cells, seminiferous tubule, and germinative layer thickness were lowered as compared with the control group. However, there were no significant differences between the P and PM groups in regard to these parameters. Melatonin preserved Sertoli cell and spermatogonia function. The testosterone and follicle-stimulating hormone (FSH) levels were also preserved. Melatonin significantly decreased malondialdehyde (MDA) levels and preserved the antioxidant enzyme levels such as glutathione peroxidase (GPx) and nitrite nitrate ( <![CDATA[ opagenumbers NO_2^ - /NO_3^ - ]]> ). Melatonin may protect testicular functions in P treated patients and is open to consideration during chemotherapy since it appears to be without any side effects.